Correction: Amiri et al. Numerical Evaluation of the Transient Performance of Rock-Pile Seasonal Thermal Energy Storage Systems Coupled with Exhaust Heat Recovery. Appl. Sci. 2020, 10, 7771 - Leyla Amiri; Marco Antonio Rodrigues de Brito; Seyed Ali Ghoreishi-Madiseh; Navid Bahrani; Ferri P. Hassani; Agus P. Sasmito (Applied Sciences, 2025)
The authors state that this paper [...]